PERAN GURU DALAM INTERNALISASI KARAKTER PEDULI LINGKUNGAN MELALUI PEMBELAJARAN IPAS DI SDN GADING TRENGGALEK - Dina Astiari, Oktavia; Dwi Saputro, Anip; Syukroni, Azid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low attitude of environmental care in elementary school students is a problem that needs attention, considering that this attitude also determines the sustainability of environmental conservation in the future. This condition requires character education that is inseparable from the role of teachers in it. This study aims to analyze the role of teachers and describe the results, supporting factors, and inhibiting factors in internalizing the character of caring for the environment through the integration of science learning. This type of research is in the form of descriptive qualitative with data collection techniques through interviews, observations, and documentation. The results of the study show that teachers carry out their roles as educators, managers, administrators, supervisors, leaders, innovators, motivators, dynamizers, evaluators, and facilitators in an integrated manner. The process of internalizing values is carried out through three stages, namely the provision of materials, learning practices and projects, and habituation. The internalized values of caring for the environment include managing waste wisely, reducing the use of plastic waste, maintaining cleanliness, greening and plant care. The internalization results show that students are able to understand and apply values in daily life at school. The internalization process is supported by the example of teachers, the use of varied and contextual learning methods and media, appreciation, the environment and school programs. The obstacles found include low awareness and confidence in some students, differences in student character, and the unavailability of plastic waste processing facilities.